DESIGN OF A PROJECT MANAGEMENT SYSTEM AT CV. KHARISMA KARYA NUSANTARA USING THE CRITICAL PATH METHOD (CPM) - R, Defano Putra; Agusti, Febrina; Nurdiansari, Brilian (LPPM Universitas Duta Bangsa Surakarta, 2025)
Project delays have a substantial impact on overall implementation performance; therefore, effective control and scheduling mechanisms are essential to ensure time efficiency throughout every phase of work. CV. Kharisma Karya Nusantara frequently encounters delays caused by excessive overtime and an unstructured reporting system that cannot be evaluated in real time. This study aims to design a project management system and analyze the scheduling impact using the Critical Path Method (CPM). The CPM analysis identified a critical path consisting of preparatory work, lower structure levels 1 to 3, ground floor work, upper structure levels 1 and 2, first, second, and third floor structural works, walls and partitions of the second floor, first floor finishing, and final work. The total project duration calculated using CPM was 588 days. When recalculated using Microsoft Project, the duration was reduced to 337 days, resulting in a time efficiency of 251 days. These findings demonstrate that implementing a well-structured and integrated project management system can significantly enhance scheduling efficiency, minimize delays, and optimize overall resource utilization.